2021
DOI: 10.1111/rsp3.12334
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic growth and convergence: The role of institutions and spillover effects in Colombia

Abstract: This study analyses the relationship between institutions and economic growth at the intra-regional level in Colombia. We estimated models of economic growth augmented by an institutional variable and spatial effects. The results show that conditional convergence in regions of Colombia considering institutional and spatial effects leads to a convergence rate that is relatively higher than those found in a standard growth model. The results also show that institutions have a strong positive impact on regional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(62 reference statements)
1
5
0
1
Order By: Relevance
“…Our results are consistent with Tsangarides (2010), who pointed out that a more developed financial sector and a democratic system are the main determinants of convergence in Africa. Our findings regarding the role of institutional quality in convergence are in line with those of Aristizãbal and Garcãa (2020), which mobilized a database for 24 departments of Colombia and found that institutional quality is crucial for regional convergence in Colombia. However, institutional factors in one region have a negative effect on the economic growth of neighboring regions, a fact explained by the institutional heterogeneity of these regions.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with Tsangarides (2010), who pointed out that a more developed financial sector and a democratic system are the main determinants of convergence in Africa. Our findings regarding the role of institutional quality in convergence are in line with those of Aristizãbal and Garcãa (2020), which mobilized a database for 24 departments of Colombia and found that institutional quality is crucial for regional convergence in Colombia. However, institutional factors in one region have a negative effect on the economic growth of neighboring regions, a fact explained by the institutional heterogeneity of these regions.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…This has a dual purpose, firstly empirical, to address the issue of possible collinearity between the six subindicators of institutional quality. The second is a research interest, to conduct a comparative analysis across the different African countries in our sample in terms of institutional quality, as opposed to the majority of studies that have tackled this issue (Aristizãbal & Garcãa, 2020; Saha et al, 2022) to mobilize separate variables to assess institutional quality.…”
Section: Empirical Methodology: Data Variables and Empirical Modelmentioning
confidence: 99%
“…The latest empirical results related to convergence from outside Indonesia are results that state there is convergence, including in Europe by Kubis and Schneider (2016); Butkus et al (2018); Alexa et al (2019); Dogan and Kındap (2019); Balash et al (2020); Montresor et al (2020); Postiglione et al (2020);Demidova, (2021). In America by Yu and Lee (2012); Breau and Saillant (2016);Flores-Chamba et al (2019); Leiva and Pino (2020); Aristizábal and García (2021), in Asia by Barro (2016); Lee (2016;; ; (Mendez and Santos-Marquez, 2020). On the other hand, the results suggest a divergence by Goschin (2014;, Simionescu (2014), Pietrzykowski (2019) in Europe, Lolayekar and Mukhopadhyay (2017; in Asia, and Kant (2019) in Africa.…”
Section: The Phenomenon Of Inequality Development Between Regions Inmentioning
confidence: 99%
“…Furthermore, the latest research on the application and development of spatial convergence is carried out with different regional analysis units, including by Sanso-Navarro et al (2020) across countries worldwide, Yu and Lee (2012) in the United States, Breau and Saillant (2016) in Canada, Aristizábal and García (2021) in Columbia, Flores-Chamba et al ( 2019) in Ecuador, Leiva and Pino (2020) in Chile, Lima andNeto (2016) in Brazil, Alexa et al (2019); Balash et al (2020); Montresor et al (2020); Panzera and Postiglione (2021); Pietrzykowski (2019); Postiglione et al (2020) in the European Union region, Yildirim et al (2009); Dogan and Kındap (2019) in Turkey, Goschin (2017) in Romania, Sun et al (2017) in China, Chatterjee (2017) in India, Mendez and Santos-Marquez (2020) in the ASEAN region, and Indonesia by Vidyattama (2013); Aritenang (2014); Aspiansyah and Damayanti (2019). Empirical results show that geographically weighted regression increases the model's better explanatory power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Colombia entre las naciones en desarrollo de la región, se ha caracterizado por un crecimiento económico relativamente estable, pero con altos niveles de pobreza y desigualdad (Han y Maisel 2018; Robinson, 2016;Aristizábal y García, 2020); estos fenómenos que no se han distribuido de forma homogénea sobre el territorio, se manifiestan como persistentes disparidades regionales en su interior. Las regiones centrales con mayor concentración de población y actividad económica como la capital Bogotá y los departamentos de Antioquia y Valle exhiben mejores indicadores de desempeño económico y social frente a otras periféricas como La Guajira, Chocó y Amazonas, que a decir de varios autores han sido desatendidas por el gobierno nacional (García, 2017;Galvis, Hahn, y Galvis, 2017;OCDE, 2018).…”
Section: Introductionunclassified